Penampilan Karakter Agronomi Galur-Galur Padi (Oryza sativa L.) Kandungan Zn Tinggi di Dataran Medium - Savira Mayani; Elia Azizah; Yamin Samaullah; Untung Susanto (Faculty of Agriculture University of Singaperbangsa Karawang, 2022)
The formation of high-zinc rice varieties that have a high zinc is still done conventionally namely by crossing rice line that have a high zinc. The study aimed to determine the agronomic performance, growth and genotype yield of several rice lines with high Zn content. The research was conducted in October 2020 to March 2021 at IP2TP Kuningan. The research using Augmented Design with 188 lines and 6 comparison varieties, namely A (Inpari IR Nutri Zinc), B (Inpari 45 Dirgahayu), C (Inpari 32 HDB), D (Ciherang), E (Jeliteng), F (Inpago Fortiz), then if there is real influential treatment carried out advanced analysis using LSI 5%. The result of the experiment showed that there variation in agronomic characters and genotypes significantly affect the production of some rice plants. Line 143 (IR 105947-B-59-1-1-0-1) showed the highest plant height, line 26 (IR 105739-B-26-1-2-SKI-1-SG-20-SG-1) showed the highest number of productive tillers, line 14 (IR 105739-B-26-1-2-SKI-1-SG-14-SG-1) showed the fastest flowering and harvesting age, line 176 (IR 123818-B-235-2-1-B-3) showed the highest panicle length, line 70 (IR 105730-B-79-1-4-SKI-1-2-3-2) showed the highest percentage number of filled grains per panicle, line 176 (IR 123818-B-235-2-1-B-3) showed the highest percentage number of empty grains per panicle, line 184 (IR15M1349 -SKI-2) showed the highest weight of 1000 grains, line 42 ((BP29762d-PWK-3-SKI-2-MR-7-1-1) showed the highest grain weight. Milled dry grain of 8 (IR 105774-B-46-2-1-SKI-2-SG-15-SG-G) lines is 3.09 t/ha, higher than all the comparison varieties.